2005
DOI: 10.1007/s00192-005-1366-6
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic organ prolapse and urinary incontinence in nulliparous women at the United States Military Academy

Abstract: The objective of this study was to evaluate both baseline pelvic support and incontinence in relation to physical activity in nulliparous college women. Participants were examined using the pelvic organ prolapse and quantification system (POP-Q) and completed a questionnaire. Women with stage 0 prolapse and any other stage were compared. Potential risk factors and levels of physcial activity were analyzed using the chi-square test. We evaluated 144 women. Fifty percent had stage 0 support and 50% had stage I o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 10 publications
0
21
0
5
Order By: Relevance
“…The cadets in the control group were those who either did not attend military summer training or had attended another type of training, such as air assault, jungle, or survival training school. The physical testing requirements for all cadets is the same, and baseline data previously published showed no differences in pelvic support related to activity [2]. At the time of each examination, height and weight were collected, as well as information on race.…”
Section: Methodsmentioning
confidence: 99%
“…The cadets in the control group were those who either did not attend military summer training or had attended another type of training, such as air assault, jungle, or survival training school. The physical testing requirements for all cadets is the same, and baseline data previously published showed no differences in pelvic support related to activity [2]. At the time of each examination, height and weight were collected, as well as information on race.…”
Section: Methodsmentioning
confidence: 99%
“…[23][24][25] When the patient lifted her left lower extremity approximately 5 cm from the table in the supine position, she noted "heaviness" compared to when she lifted the right lower extremity. When manual compression was applied through the ilia during the ASLR, her complaints of heaviness diminished, indicating a positive test.…”
Section: Tests and Measuresmentioning
confidence: 99%
“…P revalence rates of stress urinary incontinence (SUI) vary between 10% to 55% in women between the ages of 15 to 64 years. 2 Although SUI is a condition traditionally thought to occur in older, multiparous women, a number of descriptive studies have reported SUI in young, nulliparous women, [2][3][4]12,23 typically as an involuntary loss of urine that occurs when pressure is exerted on the bladder by sneezing, coughing, laughing, or any other physical t stuDy DEsign: Case report.…”
mentioning
confidence: 99%
“…Stress urinary incontinence (SUI) is common in women of all ages; however, female service members are particularly at risk considering the rigorous demands of military life and the stringent physical fitness requirements [1,2]. Sherman et al demonstrated the growing significance of this problem in one-third of female soldiers surveyed [3].…”
Section: Introductionmentioning
confidence: 99%